(untitled) (Experimental biology, 2016)
This investigation presents the results of analyses of anatomical, morphological and phytochemcial properties of Peganum harmala L. from southern Balkhash area. Anatomical, morphological features of the lamina, stem and the root were identified in middle-aged generative plants which have been collected during blooming and fructification phase. It was determined that some cells of the lamina contained raphides and mucous, the vein was surrounded by the major tissue of the leaf, and cells of the stem’s skin had thickened walls. In addition, a row of cells of hypodermis contained calcium oxalate, a belt of sclerenchyma cells was identified, the structure of which was flaky. Qualitative analysis of the raw materials showed 33 different types of compounds, out of which 20 were identified: 3 carbohydrates, 1 phenol, 4 phenolic and 7 amino acids, 2 flavonoids and etc. Quantitative analysis of the main groups of biologically active BAS revealed high amount of tannins, amino and free organic acids in the underground and aboveground parts, as well as the high content of alkaloids in the underground part. The aboveground part was characterized with high content of polysaccharides, in comparison to roots, and trace amount of coumarines.